Investigating the co-creation of IT consulting service value: empirical findings of a matched pair analysis - Severin Oesterle; Arne Buchwald; Nils Urbach (Electronic Markets, 2020)
Digitalization is increasingly and broadly impacting on companies throughout all industries. To cope with digital transformation, organizations need specific IT skills and often face a bottleneck between required and existing capabilities. Thus, organizations revert to support from IT consultants. However, such collaborations need to create value so as to make client organizations future-proof in the long term. We therefore need a better understanding of how value is created in IT consulting projects. We build on service-dominant (S-D) logic as the theory base and evaluate our structural model, which explains IT consulting service value based on 77 matched pairs of IT consulting projects using structural equation modeling. We provide empirical support for the assumptions of S-D logic in the IT consulting industry and reveal determinants that significantly contribute to the overall IT consulting service value. Our results contribute to the ongoing discourse in the S-D logic literature and provide meaningful insights for practice.
Keywords: L84; 620; Value co-creation; Service-dominant logic; Matched pair approach; IT consulting services